Regresi Logistik Dua Level Respon Biner untuk Pemodelan Data Status Kelulusan Mata Kuliah Statistika Mahasiswa Fakultas X, Y dan Z Universitas Islam Bandung Angkatan 2019 - Alma Mariana Sofiah; Nusar Hajarisman (Bandung Conference Series: Statistics, 2023)
Abstract. Two-level binary logistic regression is a multilevel analysis used to analyze data that has a two-level hierarchical structure with binary response data. Hierarchical data structure is data with observation units nested in higher units. Two-level regression is the simplest multilevel model where the first level is individual data and the second level is group data. In this study, we will discuss the use of two-level binary logistic regression on data on the Passing Status of Statistics Courses of Bandung Islamic University Students Class of 2019. The data used is secondary data obtained from PSITEK Bandung Islamic University, with a total data of 1173 students nested into 3 groups (Faculty). The research variable in this study is the status of passing the statistics course as the dependent variable (Y), with two categories, namely 0 for students who do not pass and 1 for students who pass, as well as gender, regional origin and GPA as predictor variables (X) at level 1 and science clumps as predictor variables (Z) at level 2. The parameter estimator is carried out using the Maximum Likelihood via Quadrature method. Based on the results of the application of 2-level binary logistic regression, the factors that influence the response are the variables of regional origin and GPA (level 1/student) and clumps of knowledge (level 2/Faculty). Abstrak. Regresi logistik biner dua-level merupakan analisis multilevel yang digunakan untuk menganalisis data yang mempunyai struktur hirarki dua level dengan data respon biner. Struktur data hirarki adalah data dengan unit-unit observasi yang bersarang pada unit yang lebih tinggi. Regresi dua-level merupakan model multilevel yang paling sederhana dimana level kesatu data individu dan level kedua data kelompok. Dalam penelitian ini, akan membahas penggunaan regresi logistik biner dua level pada data Status Kelulusan Mata Kuliah Statistika Mahasiswa Universitas Islam Bandung Angkatan 2019. Data yang digunakan adalah data sekunder yang diperoleh dari PSITEK Universitas Islam Bandung, dengan total data sebanyak 1173 mahasiswa yang tersarang kedalam 3 kelompok (Fakultas). Variabel penelitian dalam penelitian ini adalah status lulus mata kuliah statistika sebagai variabel dependen (Y), dengan dua kategori yaitu 0 untuk mahasiswa yang tidak lulus dan 1 untuk mahasiswa yang lulus, serta jenis kelamin, asal daerah dan IPK sebagai variabel prediktor (X) pada level 1 dan rumpun ilmu sebagai variabel prediktor (Z) pada level 2. Penaksir parameter dilakukan menggunakan metode Maximum Likelihood via Quadrature. Berdasarkan hasil penerapan regresi logistik biner 2-level menyatakan bahwa fakor-faktor yang mempengaruhi respon adalah variabel asal daerah dan IPK (level 1/mahasiswa) dan rumpun ilmu (level 2/Fakultas).